SINR-based conversion and prediction approach for handover performance evaluation of video communication in Proxy Mobile IPv6. (March 2019) - Hassan, Md. Mahedi; Tan, Ian K.T.; Selvaretnam, Bhawani; Poo, Kuan Hoong
Abstract: Proxy Mobile IPv6 is an operational cluster of network-based localized mobility management protocol. This protocol has numerous advantages but still suffers from long latency and degradation in performance during the handover of video transmissions. In order to minimize the latency and improve performance during handover, this paper proposes a Signal to Interference and Noise Ratio (SINR)-based conversion and prediction approach. The approach sets up a prior connection based on the mobility prediction, reduces the time to acquire information, eliminates on-the-fly packet loss, and executes horizontal and vertical handover using SINR conversion. The motivation of this paper is to simulate, analyze and evaluate the video performance over Proxy Mobile IPv6 protocol. Simulations were conducted on packet and frame metrics which are latency, cumulative jitter, packet loss, frame loss and video quality measurements that analyzes and evaluates the network performances at the mobile host and during the handover.